Vth International Conference on Environmental Mutagens in Human Populations: Introduction - (:unkn) unknown (ELSEVIER SCIENCE BV, 2008)
The Vth International Conference on Environmental Mutagens in Human Populations (VthICEMHP), 20-24 May 2007 was successfully completed in Antalya, Turkey. With approximately 200 participants from 35 countries, the conference participants enjoyed extensive exchange of scientific and cultural expertise. Like the previous conferences in this series, collaborative and sustainable projects were developed among the participants. Publications in this monograph represent outstanding reviews and experimental data from invited speakers.